Rice Planting Conditions in Bare Nuea Sub-district, Bacho District, Narathiwat Province - Thepkun, Prajak; Chelaeh, Bukhoree (Princess of Naradhiwas University Journal, 2021)
The objectives of this research were to (1) study social and economic conditions, (2) rice cultivation conditions, (3) the need for extension and (4) problems and suggestions. The study population was 250 farmers. 154 samples were determined using Yamane (1973) at a tolerance level of 0.05. Data was collected using structure interviews. The data was analyzed using descriptive statistics through a computer package. The result found that first, most of the farmers were Islamic female, age 41-50 years graduated from high school or vocational college, earned total income between 20,001 to 40,000 baht/year with 5-7 household members and owned land more than or equal to 21 rai. Second, the farmers had area of farming rice about 5 to 6 rai and had 19-27 years of experience in rice farming. They only grew rice for household consumption with rice seed transplanting method, using walking tract or to prepare the soil, grew various kind of local rice and kept the seeds for next planting. They produced rice approximately 359.59 kg. per rai. Third, the farmers need supports to improve their knowledge on quality rice production, soil preparation and postharvest management through demonstration, training, field trips with local wisdom experts or local role model farmers and agricultural officers, which the learning tools can be manual/documentation, academic articles on agriculture, brochure, media television and internet. Last, the problems and obstacles of farmers in rice planting were rice pests and insufficient water supply.